Global research trends in pre-service teacher leadership: a bibliometric analysis (2018-2024) - Abdul Razak, Amirul Fahmie; A. Ghani, Muhammad Faizal; Mohd Radzi, Norfariza; Zakariah, Nur Diyana (Journal of Education and Learning (EduLearn), 2025)
Pre-service teacher leadership is an emerging and crucial area of educational research, gaining significant attention due to its impact on future educational outcomes. The purpose of this study is to investigate research trends in pre-service teacher leadership globally from 2018 to 2024 using bibliometric analysis with the Scopus database. A total of 1278 articles were identified and examined using VOSviewer and mapping analysis. The results show a steady increase in research on pre-service teacher leadership, with the United States leading in contributions, followed by the United Kingdom. The analysis covers publication trends, types, languages, citation analysis, country collaborations, common citation networks, and topic tendencies. The study identifies key authors, their works, and their interactions. A word analysis was conducted to ascertain concepts used in the field, resulting in cognitive maps that show patterns of relationships and cooperation. The evaluation also included national partnerships, journals, authors, publications, and citation sources within the network. The findings are valuable for researchers in pre-service teacher leadership and can serve as a foundation for future studies in this field.